2009
DOI: 10.1177/0145445509348733
|View full text |Cite
|
Sign up to set email alerts
|

Group-Based Preference Assessment for Children and Adolescents in a Residential Setting: Examining Developmental, Clinical, Gender, and Ethnic Differences

Abstract: This study examines developmental, clinical, gender, and ethnic group differences in preference in residentially placed children and adolescents. In addition, this study considers whether residentially placed youth prefer stimuli currently being used as rewards as part of a campuswide token economy system and whether youth would identify preferred stimuli that are not currently offered. The article discusses a survey devised specifically for the purpose of this study. Stimuli currently offered as rewards are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Research has shown that the results of preference assessments are likely to lead to the identification of actual reinforcers (DeLeon & Iwata, ; Hagopian, Long, & Rush, ). A survey was used as the preference assessment measure because it can include a multitude of stimuli and has been successfully devised to identify preferred items for adolescents and children (e.g., Cautela & Lynch, ; Jones, Mandler‐Provin, Latkowski, & McMahon, ; Resetar‐Volz & Cook, ). The preferred items and activities identified via the preference assessments were included in each of the participants’ reward menus.…”
Section: Interventionmentioning
confidence: 99%
“…Research has shown that the results of preference assessments are likely to lead to the identification of actual reinforcers (DeLeon & Iwata, ; Hagopian, Long, & Rush, ). A survey was used as the preference assessment measure because it can include a multitude of stimuli and has been successfully devised to identify preferred items for adolescents and children (e.g., Cautela & Lynch, ; Jones, Mandler‐Provin, Latkowski, & McMahon, ; Resetar‐Volz & Cook, ). The preferred items and activities identified via the preference assessments were included in each of the participants’ reward menus.…”
Section: Interventionmentioning
confidence: 99%
“…Accordingly, behavior analysts who rely on edible reinforcers should consult with families about which edible stimuli are likely to function as potent reinforcers according to culturally based food preferences and whether specific edibles are permissible during teaching sessions. Although additional research is needed, Resetar Volz and Cook (2009) found there was a statistically significant difference between restaurant and food preferences for children and adolescents of different ethnicities. Resetar et al’s (2009) findings suggest that clinicians should consider including ethnic food choices in preference assessments.…”
Section: Federal Requirementsmentioning
confidence: 93%
“…Although additional research is needed, Resetar Volz and Cook (2009) found there was a statistically significant difference between restaurant and food preferences for children and adolescents of different ethnicities. Resetar et al’s (2009) findings suggest that clinicians should consider including ethnic food choices in preference assessments. BCBAs who successfully communicate with ELL clients through the aid of an interpreter may mitigate these challenges by fully understanding the nature of the individual’s reinforcer and language preferences.…”
Section: Federal Requirementsmentioning
confidence: 93%
“…Research has shown that the results of preference assessments are likely to lead to the identification of actual reinforcers (DeLeon & Iwata, ; Hagopian, Long, & Rush, ). A survey was used as the preference assessment measure because it included a multitude of stimuli and has been successfully devised to identify preferred items for adolescents and children (e.g., Resetar‐Volz & Cook, ). The preferred items and activities identified via the preference assessments were included in each of the participant's reward menus.…”
Section: Methodsmentioning
confidence: 99%